Student perceptions towards the usage of AR-supported STEMUP application in mobile courses development and its implementation into English learning - Lin, Huang-Yao; Tsai, Shu-Chiao (Australasian Journal of Educational Technology, 2021)
This study investigated the use of an augmented reality (AR) -supported application called STEMUP to develop mobile English courses on Android and iOS smartphones. It focused on vocabulary and listening and speaking skills, in an initial assessment of the effectiveness of implementing AR-based mobile English courses. The study was conducted with English major sophomores who took an elective course, Design and Practice of Mobile Learning, at a technology university in Taiwan. A preliminary curriculum was prepared for integrating STEMUP into English courses in which students would not only learn how to develop AR-based mobile English courses but also practise target English skills with two assigned English courses on STEMUP. The results from the student questionnaire indicated that the layout design of the student-generated AR-based mobile English courses complied with several of Mayer’s principles of multimedia learning and that the focus on learning with the mobile English courses met Chapelle’s seven suggested criteria for the development of multimedia computer-assisted language learning. The students of English as a foreign language responded that STEMUP was an easy application for developing AR-based mobile English courses and that learning with the assigned AR-based mobile English courses was interesting and motivational. Implications for practice or policy: Teachers of English as a foreign language can easily develop AR-based mobile English courses on STEMUP by referring to Mayer’s principles of multimedia learning. Focusing on learning English language with AR-based mobile courses meets Chapelle’s suggested criteria for development of multimedia computer-assisted language learning. This AR-supported STEMUP can be extended to educational settings, especially in remote schools that lack English learning resources and teachers.